Spectrophotometric Determination of Tiapride in Pharmaceutical Formulations - A. Alarfaj, Nawal; A. Mostafa, Azza; A. Alghamdi, Zinah (Asian Journal of Chemistry, 2013)
Simple, accurate and precise spectrophotometric method is presented for the determination of tiapride in its pharmaceutical formulations. The method is based on the reaction of the aliphatic amino group on tiapride as n-electron donor with p-chloranilic acid as a p-acceptor in acetone to yield a reddish coloured charge transfer complex product which absorbed at 520 nm. Beer's law is obeyed in the concentration range 10-100 μg/mL of tiapride with a correlation coefficient of 0.9999. The optimum experimental parameters for the reaction have been studied. Statistical analysis of the results has been carried out revealing high accuracy and good precision. The suggested procedure could be used for the determination of tiapride in its pharmaceutical tablets.